Ketahanan Beberapa Klon Kentang (Solanum tuberosum L.) terhadap Asam Fusarat dan Penyakit Busuk Kering Umbi - Sari, Dewi Citra; Dinarti, Diny; Suwarno, Willy Bayuardi; Purwito, dan Agus (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTFusaric acid produced by Fusarium spp. played a major role in potato dry rot development. Using fusaric acid as a selection agent may be useful to identify resistant clones. The aim of this experiment was to evaluate the morphological responses of 10 potato clones (Granola, Atlantic, Cipanas, DTO 28, DTO 33, Russet Burbank, IPB 1, CIP 801040, CIP 801045, dan CIP 801050) and their resistance level to fusaric acid and Fusarium solani. The research was conducted in Plant Breeding Laboratory and Tissue Culture Laboratory 3, Departement of Agronomy and Horticulture from April 2014-February 2015. The in vitro experiment was arranged in a randomized block design with 4 fusaric acid concentrations and 4 replications, while the F. solani infection experiment was arranged in a completely randomized design with 5 replications. The result showed that fusaric acid inhibits growth, reduce microtubers production, and caused planlets death. Correlation analysis between in vitro resistance to fusaric acid and F. solani infection on tuber showed positive and notable result. Accordingly, fusaric acid can be used to identify any clones resistant to F. solani.Keywords: Fusarium solani, phytotoxin, selection